Digital eye strain: prevalence and associated socio-demographic factors among banking assistants in Colombo District, Sri Lanka - Supipi Dissanayake Gunawardana; Dushyanthi Jayawaradana (Journal of the College of Community Physicians)
Introduction: Along with the technological advancement, many sectors had digitalized including banking, education and health sectors. With the excess usage, digital eye strain is now becoming the most common occupational hazard among the digital device users. Objectives: To determine the prevalence of banking assistants with the digital eye strain (DES) and associated socio-demographic factors among banking assistants in a divisional secretariat division in Sri Lanka Methods: A descriptive cross-sectional study was done among all the branches of randomly selected banks in a purposively selected divisional secretariat division. On selected banks, 372 eligible banking assistants were selected by systematic sampling. Data were collected by a structured pretested self-administered questionnaire. DES was detected using Computer Vision Syndrome Questionnaire (CVS-Q). Selected factors were cross-tabulated by the presence or absence of DES and the association was assessed using Chi-squared followed by multiple logistic regression. A p value of 0.05 was used to determine the significance. Results: The response rate was 94.08%. The mean age of study population was 32.5 (95% CI: 31.88-33.11) years. Majority were females (n=206; 58.9%), married (n=228; 65.4%) and had a university degree (n=175; 50%). The duration of employment of the banking assistance varied from 3 months to 15 years. Sixty percent (n=210) of the banking assistants worked in the financial section. DES was detected in 70.6% of the employees. Civil status (p<0.001), education level (p=0.014) and working section (p=0.039) were found to be significantly associated with the presence of DES. Conclusions & Recommendations: The prevalence of DES among banking assistants was notably high. Early detection efforts should prioritize married employees, those in operational roles, and non-graduates to mitigate the condition's impact.